2014 IEEE 22nd International Symposium on Modelling, Analysis &Amp; Simulation of Computer and Telecommunication Systems 2014
DOI: 10.1109/mascots.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Perspective of Disk vs. Flash Media in Archival Storage

Abstract: For three decades, Kryder's law correctly predicted an exponential increase in bit density on disk platters, leading to an exponential drop in cost per gigabyte, and thus to an entrenched expectation that if data could be stored for a few years the incremental cost of storing it forever would be minimal. However, disk now is over 7 times as expensive as Kryder's law would have predicted, and industry projections suggest that in 2020 the gap will reach 200 times, disrupting this expectation.Our model shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Other study highlighted that over the long term owning the infrastructure can save money [88]. Finally, researchers that studied the endowment model over a 100 years simulated archive founded that SSDs are a better choice media to keep the costs low [89].…”
Section: Financial and Budgetary Issuesmentioning
confidence: 99%
“…Other study highlighted that over the long term owning the infrastructure can save money [88]. Finally, researchers that studied the endowment model over a 100 years simulated archive founded that SSDs are a better choice media to keep the costs low [89].…”
Section: Financial and Budgetary Issuesmentioning
confidence: 99%
“…We also tested SSD characteristics since it had been shown that flash may be suitable for archival storage over time while keeping the costs comparable to traditional disk archives [31]; also there is increasing interest in designing flash to be used for archival purposes [21] and industry is looking at incorporating flash in their archival storage systems [26,55].…”
Section: Prolonged Media Usagementioning
confidence: 99%
“…Storage costs are approximately one third of the total system's cost [41,46], and they are going to be more important in the future as the annual media density growth rate (Kryder's rate, or K r ) continues to decrease [31,46]. In times of highly increasing media density growth, it was cost-effective to replace media before the manufacturer-supplied endof-life, and not much thought was given to the planning duration or using media for an extended period of time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For all other uses, contact the owner/author(s). time, price per unit of storage on commodity hardware has been seeing a significant decrease as suggested in [15], enabling new use cases.…”
Section: Introductionmentioning
confidence: 99%